2018
DOI: 10.26442/terarkh201890770-76
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin Receptor Agonists in the Treatment of Chronic Resistant Primary Immune Thrombocytopenia: Efficacy and Safety Data in Real Clinical Practice

Abstract: Objective: To analyze the long-term efficacy and safety of ATR in adult patients with primary resistant ITP in real-world clinical practice. Materials and methods.The article contains long-term results analysis of ATR application under real clinical practice conditions in 138 patients (40 men and 98 women) whose median age at the beginning of therapy was 59 (18-86) years. Two ATR medicines-romiplostim (100 patients) and eltrombopag (38 patients) were used. Results. During the first month of therapy, the median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Eltrombopag and romiplostim are effective drugs that have been established as a mainstay in the treatment of patients with ITP providing an excellent long-term outlook. Response rates from clinical trials 79 and clinical practice data 20 do not seem to differ greatly between both agents, though none of the studies provided a randomized comparison. Thus, the choice between eltrombopag and romiplostim is a matter of availability, convenience and cost.…”
Section: Discussionmentioning
confidence: 99%
“…Eltrombopag and romiplostim are effective drugs that have been established as a mainstay in the treatment of patients with ITP providing an excellent long-term outlook. Response rates from clinical trials 79 and clinical practice data 20 do not seem to differ greatly between both agents, though none of the studies provided a randomized comparison. Thus, the choice between eltrombopag and romiplostim is a matter of availability, convenience and cost.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is still hard to draw a conclusion, since eltrombopag is mainly used for increasing the platelet count but not for blood pressure regulation. Although increased blood pressure presents as an adverse event in some patients, the mechanism is not clear yet (Ptushkin et al, 2018). It is worth exploring how eltrombopag functions after binding to ACE2, which can help us further understand the potential anti-SARS-CoV-2 mechanism of eltrombopag and its adverse effect of increasing the blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have concluded that romiplostim and eltrombopag are generally well-tolerated medications [ 19 , 27 , 28 ]. However, some adverse effects have been reported.…”
Section: Reviewmentioning
confidence: 99%